2012
DOI: 10.1007/978-3-642-23029-5
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Wave Propagation and Scattering in the Heterogeneous Earth : Second Edition

Abstract: Scattering due to randomly distributed small-scale heterogeneities in the earth significantly changes seismic waveforms of local earthquakes especially for short periods. Scattering excites long lasting coda waves after the direct arrival and broadens the apparent duration of oscillation with increasing travel distance much longer than the source duration time. Models of propagation through deterministic structures such as those with horizontally uniform velocity layers cannot explain those observed phenomena.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
397
1
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(414 citation statements)
references
References 333 publications
(600 reference statements)
11
397
1
5
Order By: Relevance
“…Numerical simulations have shown that topography such as that found at The Geysers can cause variations in the amplitudes of seismic waves of more than 50 % at frequencies above 2 Hz (BOORE 1972(BOORE , 1973BOUCHON et al 1996). The effects of heterogeneity in velocity has also been investigated with numerical calculations (FRANKEL and CLAYTON 1986;O'CONNELL 1999;SATO et al 2012) and effects similar to those shown in Fig. 7 can be produced by velocity variations of only about 5 %.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Numerical simulations have shown that topography such as that found at The Geysers can cause variations in the amplitudes of seismic waves of more than 50 % at frequencies above 2 Hz (BOORE 1972(BOORE , 1973BOUCHON et al 1996). The effects of heterogeneity in velocity has also been investigated with numerical calculations (FRANKEL and CLAYTON 1986;O'CONNELL 1999;SATO et al 2012) and effects similar to those shown in Fig. 7 can be produced by velocity variations of only about 5 %.…”
Section: Resultsmentioning
confidence: 94%
“…For instance, the observed seismograms in Fig. 7 show many of the features considered by SATO et al (2012) as indicative of high frequency scattering by correlated random heterogeneity, including the codas of P and S waves that last longer than the expected source duration, an S coda that is more prominent than that of P, and a tendency for equipartition of motion on the different components. The fact that the seismograms at each station have certain distinctive characteristics, such as frequency content, shape of phase arrivals, and duration of phases, that are independent of the source suggests that much of this scattering is taking place near the seismic station.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the propagation of classical waves through strongly scattering media is of great importance for many applications such as imaging, characterization, or communication with all kinds of waves [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Random inhomogeneities inside the Earth's lithosphere scatter high-frequency seismic waves and thereby cause phenomena such as the attenuation, dispersion, and generation of coda waves (Sato et al, 2012). The modeling of such inhomogeneities can be categorized into two concepts: random spatial fluctuation of medium parameters (called random media), and discrete scatterers such as cracks, inclusions, or cavities.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of such inhomogeneities can be categorized into two concepts: random spatial fluctuation of medium parameters (called random media), and discrete scatterers such as cracks, inclusions, or cavities. Although the concept of random media has been popularly adopted in theoretically modeling seismic scattering (Sato et al, 2012), it assumes quite often a continuous heterogeneity. In contrast, the real Earth's interior obviously has a discontinuous nature.…”
Section: Introductionmentioning
confidence: 99%